Chromium induced changes in growth and physiological attributes of Chicory (Cichorium intybus L), an important medicinal plant - Kouser, Ashyana; Khan, Athar Ali (Plant Science Today, 2021)
This study was conducted to determine the impact of different concentrations (25, 37.5 and 50 mg kg-1 soil) of chromium (Cr) on growth, photosynthetic pigments, protein content, proline content, activities of antioxidant enzymes and seed yield of Cichorium intybus in a pot experiment. The results revealed that all the Cr treatments significantly (P </= 0.05) reduced the growth, photosynthetic pigments (chlorophyll a, chlorophyll b and total chlorophyll and carotenoids contents), protein content and seed yield in C. intybus. The activities of catalase (CAT), superoxide dismutase (SOD), peroxidase (POD) and proline content in C. intybus leaves increased significantly (P </= 0.05) with increasing levels of Cr treatments. Cr accumulation was found greater in the roots than in the shoots and enhanced with increasing Cr concentrations. Hence, C. intybus may serve as a bio-meter of Cr in Cr contaminated soils.